How to find out about economics - Parsons, Stanley Alfred James (Oxford ; New York : Pergamon Press, 1972)
This book has been arranged according to the Dewey Decimal Classification, which is used by many libraries. The aim has been to provide a form of spectrum in each case to indicate the range of titles available.
Includes bibliographical references and index.
ne 27/08/2021
Loans
Keywords: Economics